Teungku’s Role in Education in Dayah (Pesantren) Tradition in Acehnese Society - Jannah, Rauzatul; Munirah, Munirah; Nasution, Riska Khairani; Aini, Dalilan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to explore and analyze the role of teungku in education in the Dayah Tradition in Acehnese society. The Dayah tradition is a habit carried out by students in behaving towards teungku (teachers). Teungku, as a respected religious figure and considered to have religious authority, plays a central role in dayah especially in the field of education. This study used phenomenological methods and history methods. The source of data in this study is informants, who were selected by purposive sampling, namely several teungku in the Aceh region. Data collection was carried out observation, interview, and documentation techniques. The collected data were analyzed qualitatively using a descriptive-analytical approach. The results of the research show that teungku is very influential on the progress of education and plays an active role in advancing dayah education in Aceh selflessly with invaluable sincerity capital..